2011
DOI: 10.1111/j.1600-0528.2011.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride content of Ready‐to‐Feed (RTF) infant food and drinks in the UK

Abstract: The results suggest that the F concentrations of UK-marketed RTF infant foods, drinks and formula milk are not sufficiently high to be a risk factor for dental fluorosis, if consumption is within the limits recommended for infants and young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
4
17
1
Order By: Relevance
“…In the present study, the lowest fluoride concentrations were observed for cow's milk represented by whole, semiskimmed, and skimmed groups (0.02, 0.02, 0.03 μg F/mL, respectively). These values did not show risk to fluorosis development, and previous studies found similar results with a medium F content of 0.028 μg/mL (22).…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, the lowest fluoride concentrations were observed for cow's milk represented by whole, semiskimmed, and skimmed groups (0.02, 0.02, 0.03 μg F/mL, respectively). These values did not show risk to fluorosis development, and previous studies found similar results with a medium F content of 0.028 μg/mL (22).…”
Section: Discussionsupporting
confidence: 86%
“…When reconstituted with fluoridated water (typically containing 1 mg F/l), the F concentration of IMF ranges from 0.49 to 1.53 mg/l [20,21]. Fluoride levels of ready-to-feed infant milks are significantly lower, up to 0.030 mg/l [22]. The levels of F in raw fruits and vegetables as well as in unprocessed foods and beverages are low.…”
Section: Exposure To F and Its Sourcesmentioning
confidence: 99%
“…The food diaries were collected during studies conducted between 2003 and 2014 [Zohouri et al, 2006;Maguire et al, 2007] and consequently analysed to identify the most consumed food and drink items and the core contributors to dietary F intake in this age group [Zohouri et al, 2003[Zohouri et al, , 2006Maguire et al, 2007Maguire et al, , 2012Zohoori et al, , 2013Zohoori et al, , 2014Omid et al, 2015].…”
Section: Methodsmentioning
confidence: 99%
“…Over time, with enhancement of the analytical methods used for F analysis with improved detection limits, as well as dietary changes towards the consumption of more ready-to-consume food and drink products, an F database needs to remain current and it is important that it reflects items commonly consumed by the population it serves. A range of research projects on the F intake of infants and young children, conducted in the UK since 2003 [Zohouri et al, 2003[Zohouri et al, , 2006Maguire et al, 2007Maguire et al, , 2012Zohoori et al, 2012Zohoori et al, , 2013Zohoori et al, , 2014, have provided the information and opportunity to derive a current and comprehensive F database. This paper briefly describes the analysis of the F contents of 518 different food and drink products available on the UK market and subsequent development of the F database .…”
mentioning
confidence: 99%